Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung - Beutner, Marc; Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

EU-StORe- Creating European Standards for Open Education and Open Learning Resources - Schneider, Jennifer Nicole

Research on didactical material and open learning resources - Schneider, Jennifer Nicole

Training Courses and Implementation - Schneider, Jennifer Nicole

The EU-StORe-Survey - Schneider, Jennifer Nicole

Evaluation of the first Prototype version of AGnovel - Schneider, Jennifer Nicole

Evaluation - Schneider, Jennifer Nicole

Musical Representations of the Seraglio in Eugène Scribe’s Vaudeville L’ours et le pacha and in its Adaptions in Nineteenth-Century European Theatre - Münzmay, Andreas (Images of the Harem in Literature and Theatre)

Faire parler l’hypertextualité - Münzmay, Andreas (Parodier l’opéra. Pratiques, formes et enjeux)

What Affects Students’ Computer and Information Literacy around the World? – An Analysis of School and Teacher Factors in High Performing Countries - Lorenz, Ramona; Eickelmann, Birgit; Gerick, Julia (Proceedings of Society for Information Technology & Teacher Education International Conference 2015)

Geschlechteridentitäten von Jugendlichen im Kontext von Social Media. Jahrestagung der Fachstelle Gender NRW (FUMA) am 26. Juni 2014 in der Volkshochschule Düsseldorf - Richter, Susanne (GENDER – Zeitschrift für Geschlecht, Kultur und Gesellschaft)
Zusammenfassung Auf der Tagung der Fachstelle Gender NRW (FUMA) „Geschlechteridentitäten von Jugendlichen im Kontext von Social Media“, die am 26.06.2014 in Düsseldorf stattfand, stand der Umgang mit neuen Medien im Mittelpunkt. Diskutiert wurden die Praktiken von Jugendlichen in sozialen Netzwerken und die Herausforderungen, die sich hieraus für Mitarbeitende der Kinder- und Jugendhilfe ergeben. Dabei wurde auch der Frage nach Auswirkungen auf Geschlecht und Geschlechtsidentitäten nachgegangen. Schlüsselwörter Internet, Neue Medien, Web 2.0, Pädagogik, Jugendarbeit, Geschlechtsidentität Summary Adolescent Gender Identities in the Context of Social Media. Annual conference of the specialist department Gender NRW (FUMA), Düsseldorf, 26 June 2014. The conference “Adolescent Gender Identities in the Context of Social Media” was held in Düsseldorf on 26 June 2014 and was hosted by the specialist department Gender NRW (FU-MA). It focused on the use of new media. Participants discussed adolescents’ practices in social networks and the resulting challenges for youth work professionals. The influence on gender and gender identity was also investigated. Keywords internet, new media, web 2.0, science of education, youth services, gender identity

Tagungsbericht: Utopie & Alltag. Perspektiven auf Ideal und Praxis im 20. Jahrhundert, 23.04.2015 – 24.04.2015 Potsdam (gem. mit Janine Funke, geb. Noack) - Schmitt, Martin (H-Soz-Kult)

Fusionen von Sportvereinen – eine organisationssoziologische Betrachtung - Meier, Heiko; Adolph-Börs, Cindy; Riedl, Lars (Sciamus - Sport und Management)
Die Fusion von Sportvereinen stellt keine Seltenheit im organisierten Sport dar. Dennoch ist dieses Phänomen bislang gänzlich unerforscht geblieben. Auf der Grundlage einer organisationssoziologischen Analyse der Strukturbesonderheiten von Sportvereinen werden zunächst Probleme und Risiken von Vereinsfusionen erörtert und daran anschließend Bedingungen des Gelingens derartiger Vorhaben aufgezeigt.
Keywords: Fusion; Sportverein; Sportentwicklung; Entscheidungstheorie; Veränderungsmanagement

Computer use in class: the significance of educational framework conditions, attitudes and background characteristics of teachers on a level of international comparison - Drossel, Kerstin; Eickelmann, Birgit; Gerick, Julia (IFIP TC3 Working Conference: A New Culture of Learning: Computing and next Generations)

Bericht: Happy und klug werden – Bibelarbeit auf dem Weg - Breckner, Anne

Westfälisch-lippische Tagespresse im Vorfeld des Ersten Weltkriegs: ein Faktor der außenpolitischen Dramatisierung und des Kriegsausbruchs? - Heerdegen, Björn; Kulüke, Jan; Neuwöhner, Benedikt; Müller, Sebastian (Paderborner Historische Mitteilungen)

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience

Analytische Herleitung der Reihenfolgeregeln zur Entzerrung hochauslastender Auftragsmerkmale - Markwart, P.

12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, M.; Meyer auf der Heide, Friedhelm

Bildungspolitische Voraussetzungen für sprachbildenden Unterricht in den Fächern des Fächerverbundes Gesellschaftslehre/Gesellschaftswissenschaften - Altun, Tülay; Günther, Katrin; Oleschko, Sven (Deutsch als Zweitsprache in allen Fächern. Konzepte für Lehrerbildung und Unterricht. Beiträge zu Sprachbildung und Mehrsprachigkeit aus dem Modellprojekt ProDaZ)